2020
DOI: 10.1021/acsanm.0c00010
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Bactericidal Effect of Polyion Complex Nanoparticles on Gram-Negative Bacteria

Abstract: There is urgent need for effective bactericidal agents for use in real commercial formulations since many old disinfectants, such as halogenated compounds, are now banned. Cationic polymers may have good bactericidal properties in pure water or buffer, but typically become ineffective in the presence of anionic surfactants that are widely used in many commercial formulations. Here, we discover that polyion complex (PIC) nanoparticles formed by cationic polymers of Poly(3-AcrylaMidoPropyl) TriMethylAmmonium chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The authors described that changes in hydrophobicity had little influence on the biological property of nanoparticles. A model bacterium ( Escherichia coli ) was used to assess the disinfectant power, and the results showed a rapid inhibitory effect (> 99.99% of death within 10 min of treatment) [ 74 ] Biogenic nanoparticles Iron Silver The authors synthesized via FeG nanoparticles co-doped with Mn-Ag from the extract of Solanum trilobatum leaves. The characterization of the nanoparticles indicated iron particles in a spherical shape.…”
Section: Nanotechnology Strategies For Disinfection Of Surfaces and Pmentioning
confidence: 99%
“…The authors described that changes in hydrophobicity had little influence on the biological property of nanoparticles. A model bacterium ( Escherichia coli ) was used to assess the disinfectant power, and the results showed a rapid inhibitory effect (> 99.99% of death within 10 min of treatment) [ 74 ] Biogenic nanoparticles Iron Silver The authors synthesized via FeG nanoparticles co-doped with Mn-Ag from the extract of Solanum trilobatum leaves. The characterization of the nanoparticles indicated iron particles in a spherical shape.…”
Section: Nanotechnology Strategies For Disinfection Of Surfaces and Pmentioning
confidence: 99%
“…Considering that bacterial adhesion is the critical first step for biofilm formation, inhibition of bacterial adhesion is an attractive approach to the prevention of surface biofouling. Currently, there are several proposed approaches to create such an antibacterial surface. One of these methods is to chemically modify the material surface with the functionalization or immobilization of various antimicrobial agents, including metal nanoparticles, antimicrobial compounds, and quaternary ammonium compounds. , For example, Yang and coworkers functionalized the polyvinyl chloride surface with an antioxidant precursor N -acetylcysteine by plasma immersion ion implantation treatment, and this caused significant reduction in biofilm viability for both Gram-positive and Gram-negative bacteria . Chen et al studied the effect of surface-tethered functional peptides with different poly­(ethylene oxide) (PEO) chain lengths on cell behaviors and found that the medium-length PEO assisted the functional peptides to achieve optimal antifouling behavior .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recently, the approach has been extended to block copolymers with specic sequences, 22,23 branched polymers, [24][25][26] comb-like polymers, 27,28 polymer assemblies and micelles, 29,30 and single-chain polymer nanoparticles. [31][32][33] In addition, polymers with facially cationic amphiphilicity in the side chains have shown to promote effective interactions of the polymer with the bacterial cell membrane, causing subsequent membrane disruption. 34 While these cationic amphiphilic copolymers and macromolecules are promising platforms, the sequences of natural AMPs contain functional groups other than cationic and hydrophobic residues, and these functional groups control their stability of active conformations and specicity toward bacterial cell membranes.…”
Section: Introductionmentioning
confidence: 99%